2012
DOI: 10.1029/2012jd018163
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative aging of mixed oleic acid/sodium chloride aerosol particles

Abstract: .[1] Studies of the oxidative aging of single mixed component aerosol particles formed from oleic acid (OL) and sodium chloride over a range of relative humidities (RH) and ozone concentrations by aerosol optical tweezers are reported. The rate of loss of OL and changes in the organic phase volume are directly measured, comparing particles with effloresced and deliquesced inorganic seeds. The kinetics of the OL loss are analyzed and the value of the reactive uptake coefficient of ozone by OL is compared to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 90 publications
6
69
0
Order By: Relevance
“…As a second set of data, we considered the oxidative aging of oleic acid/sodium chloride particles [19,20]. In this experiment, a trapped particle consisting of a sodium chloride core and a thick oleic acid coating is exposed to ozone.…”
Section: Analysis Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…As a second set of data, we considered the oxidative aging of oleic acid/sodium chloride particles [19,20]. In this experiment, a trapped particle consisting of a sodium chloride core and a thick oleic acid coating is exposed to ozone.…”
Section: Analysis Of Datamentioning
confidence: 99%
“…If the droplet is assumed to be both homogeneous and spherical, the resonance wavelengths of WGMs can be used to simultaneously determine both radius and refractive index with very high precision [7,12,14]. Then, the fundamental processes of evaporation/condensation, phase change, and oxidative aging can be directly studied through changes to the radius or refractive index of a particle [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…82,93 Additionally, Reid and coworkers investigated oxidative aging of aerosol particles containing environmentally relevant organic acids using optical tweezers and cavity enhanced ringdown spectroscopy. 94,95 For mixed NaCl/oleic acid particles, they report an uptake coefficient of 2.3 Â 10…”
Section: à3mentioning
confidence: 99%
“…Studies on single particles, confined within optical or electrodynamic traps, now provide precise measurements of aerosol refractive indices and phases, hygroscopic growth, evaporation of semi-volatile components, and other properties of importance for their atmospheric behaviour. [2][3][4][5][6] These trapping-based techniques are most applicable to single particles with radii greater than 1 μm, but the smaller accumulation mode particles are of greater significance for atmospheric processes. 4 In a recent publication, we demonstrated that absolute extinction cross sections for single submicron radius spherical aerosol particles can be measured with high precision by combining optical confinement and levitation of a particle with cavity ring-down spectroscopy (CRDS).…”
Section: Introductionmentioning
confidence: 99%